Medieval literature in French lessons: a corpus to be re-evaluated - Burg, Gaëlle (Swiss Journal of Educational Research, 2022)
The literary corpus traditionally taught in secondary and higher education in French class most often comes from the literature of the 19th, 20th and 21st centuries, less often from the works of the 16th, 17th and 18th centuries, and almost never from medieval texts. Several factors may explain this observation: the apparent inaccessibility of these texts, the barrier represented by the ancient language, teachers' lack of knowledge of medieval literature, the absence of this literature in schoolbooks, or even in research in foreign language didactics. This article proposes an analysis of the literary corpus taught in French classes (secondary and higher education in France, Germany and Switzerland) and suggests ways to develop a didactic approach to ancient texts.